Review of the Year 1932 - Crum, W. L.; Hubbard, J. B. (The Review of Economics and Statistics, 1933)
THE downward course of general business in the United States continued, with two moderate interruptions, during I932. Although the total decline for the year was large, it was somewhat smaller than that of I93I; and the average rate of decline was much slackened after the first quarter. Of the two interruptions to the decline, that of April was cut short by the second gold panic, and that of December occurred under conditions more generally favorable to sustained recovery (Chart i, p. 9). Whereas in I93I the dominant factor in renewing and prolonging the decline of business had been the world financial crisis, the critical influences during I932 were mainly domestic and centered about the second-quarter crisis in the federal budget. This crisis was accompanied by a second drive upon our gold standard, an episode following so closely upon the gold panic of September-October I93I that certain effects of the two episodes upon our credit and financial situations were all but continuous. The year was marked by steady and rapid decline in short term money rates; and the aggregate reduction for the year was greater than in the calendar year I930, though not as great as for the I2-months period ending in September I930. Even during the gold panic of the second quarter money rates fell, in response to the energetic easy money policy of the federal reserve system. With the passing of the second gold crisis, credit conditions improved; and the third and fourth quarters witnessed a vigorous upturn of member bank deposits, while loans were still declining. Many credit difficulties remain unsolved, but readjustment in bank credit has gone far and provides a basis for revival of business borrowing. Average wholesale commodity prices declined further during the year, but the total drop was only about half that suffered in I93I. Although the course of prices was downward as the year closed, there had been an important gain after the end of the gold panic. Hence the December figure was only moderately below that for June, and the last half of the year as a whole gave emphatic evidence of a slackening in the long slump of prices. In security prices the final half year was even more favorable: after the May-June panic had forced both bonds and stocks to extremely low levels, brisk recoveries occurred in the third quarter, and only moderate changes took place thereafter. Average prices of both bonds and stocks closed the year not greatly changed from the levels of January. In security markets, I932 brought striking evidence of a turn for the better.